Hybrid-mode control for grid-connected inverters and characteristics comparison with current-source mode and voltage-source mode - Feng Han; Xing Zhang; Ming Li (International Journal of Electrical Power & Energy Systems)
The grid-connected inverters (GCIs) controlled by traditional Current-Source Mode (CSM) and Voltage-Source Mode (VSM) face challenges in simultaneously meeting the requirements for small-signal stability, power-response, and grid-support. The CSM-controlled GCI excels in small-signal stability and power-response performance under strong grid conditions, while the VSM-controlled GCI offers better small-signal stability and grid-support capability under weak grid conditions. To address these challenges, the paper proposes a Hybrid-Mode (HBM) control scheme for GCIs, which combines the characteristics of CSM and VSM through weighted modulation. Based on the state-space model, a thorough investigation is conducted to explore the dynamic and steady-state characteristics of the proposed control scheme, along with strategies for further improvements. Detailed comparisons with CSM and VSM were made, and the results demonstrated that the proposed HBM control offers advantages in small-signal stability, power-response performance, and grid-support capability. The simulation and experimental results have demonstrated the effectiveness of the proposed control.